Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Koperasi Simpan Pinjam di Kota Bandung - R. Ait Novatiani; Apriwandi (Owner : Riset dan Jurnal Akuntansi, 2023)
This research has a purpose, namely to analyze corporate social responsibility (CSR), the financial performance of cooperatives and the influence of corporate social responsibility (CSR) on the financial performance of cooperatives. Corporate Social Responsibility (CSR) and Financial Performance of Savings and Loan Cooperatives are the objects of research. The survey method is used in research conducted by researchers.Based on the results of the study concluded, namely: 1). implementation of corporate social responsibility (CSR) is adequate 2). the implementation of the cooperative's financial performance is adequate; and 3). the application of corporate social responsibility (CSR) affects the financial performance of cooperatives